ANALYSIS OF FARMERS' INTERNAL FACTORS WITH THE ABILITY TO KNOW HAZARDOUS MATERIALS - Eko Prasetya Widianto; Suhari Suhari; Rizeki Dwi Fibriansari; Arista Maisyaroh (LPPM Politeknik Kesehatan Kerta Cendekia, 2020)
Background: Work in agricultural areas is one of the occupations that are at risk with the accident and death rates. Hazardous and toxic material is one of the risks that can threaten the health of farmers, which is very important to be known by farmers. Objectives: This study aimed to analyze the internal factors of farmers on the ability to recognize hazardous and toxic materials. Methods: The design of this study used descriptive correlation design. Population in this study are farmers who are members of farmer groups in the working area of the Department of Agriculture in Lumajang Regency who are members of a joint group of farmers under the guidance of the Agriculture Office of Lumajang Regency. The sampling technique in this study used simple random sampling obtained samples were 45 farmers. Instrument of this study demographic data of the respondents and questionnaire that was adopted from PP No. 74, 2001 concerning the management of hazardous and toxic materials in agricultural areas. The questionnaire consists of 25 items with Cronbach Alpha .726. The data of this study were analyzed by one-way ANOVA. Results: Based on the results of the study found that two internal factors of farmers related to the ability of farmers to recognize hazardous and toxic materials in agricultural areas, namely education and work tenure, with a significance level of 0,000 less than 0.05. Education and work tenure of farming affect the experience of farmers so that the level of knowledge of farmers increases. Farmers are more aware of the effects of hazardous and toxic substances on their health according to their level of knowledge. Conclusion: Prevention of poisoning due to hazardous and toxic substances in agricultural areas can be developed by increasing health promotion and increasing farmers' knowledge to become more familiar with hazardous and toxic substances on label recognition, composition, mixing storage and their effects on health.